2012
DOI: 10.1159/000343822
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of a Systemic Inflammatory Response in Patients Undergoing Multimodality Therapy for Advanced Colorectal Cancer

Abstract: Objectives: The inflammation-based Glasgow Prognostic Score (GPS) is associated with outcome in a variety of cancers. This study investigated whether a modified GPS (mGPS) could predict survival in patients undergoing multimodality therapy for advanced colorectal cancer (CRC). Methods: We enrolled 245 patients with advanced CRC who received chemotherapy. The mGPS was recorded prior to first-line chemotherapy and to cytoreductive therapy including secondary surgery and/or radiofrequency ablation. The prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…The study by Inoue et al [1] reinforced previously published data from Forrest et al [9] who considered the GPS to be a useful stage-independent predictor for outcome of treatment, but failed to confirm such efficacy in the era of targeted agents.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The study by Inoue et al [1] reinforced previously published data from Forrest et al [9] who considered the GPS to be a useful stage-independent predictor for outcome of treatment, but failed to confirm such efficacy in the era of targeted agents.…”
mentioning
confidence: 78%
“…We read with great interest the article by Inoue et al [1] identifying the usefulness of the modified Glasgow Prognostic Score (GPS) as an independent prognostic indicator of survival in patients undergoing multimodality therapy for advanced colorectal cancer (CRC). This biological score has proven its efficiency as a prognostic marker in metastatic CRC (mCRC) [2], in assessing the tolerance of systemic chemotherapy [3] and as a predictor of cancer-related death after surgery [4].…”
mentioning
confidence: 99%
“…[19][20][21][22] Most notably, GPS, modified GPS (mGPS), and the Prognostic Index have been associated with cancer survival.…”
Section: Survivalmentioning
confidence: 99%
“…Many studies have shown that inflammation plays a significant role in dif-ferent stages of tumor growth like initiation, promotion, malignant conversion, invasion and metastasis [2][3][4]. Several systemic inflammatory response markers like C-reactive protein, albumin, interleukins, and tumor necrosis factors have been identified as prognostic indicators of adverse outcomes in colorectal cancer (CRC) patients [5,6]. Moreover, simple systemic inflammatory markers [e.g.…”
Section: Introductionmentioning
confidence: 99%